The roles of evaluation for vocational education and training : plain talk on the field of dreams - Grubb, W. Norton [Verfasser]; Ryan, Paul [Verfasser] (My University, 1999)
"Aimed at training policy analysts and the evaluation community at large, this book presents issues and case material that, it is hoped, may also be of interest to a wider audience of professionals and academics concerned with public policy, as well as representatives of the world of work and the world of training. Following a discussion on concepts of training, the authors essentially focus on the 'why' and 'how' of evaluation, before presenting and commenting on the results of a number of evaluation exercises. Two concluding chapters treat the use (and abuse) of evaluation results in policy making and the implications for evaluation of recent trends in vocational education and training, such as decentralization, the declining role of the State, a shift towards work-based learning and a continued concern for meeting equity objectives through training." (author's abstract, IAB-Doku) ((en)) Die Autoren diskutieren Konzeptionen von Berufs(aus)bildung und Rolle und Funktion von Evaluation in diesem Bereich. Dazu wird eine breite Palette von Evaluationsmethoden und -verfahren vorgestellt; ausserdem werden Verwendung und Missbrauch von Evaluationsergebnissen bei politischen Entscheidungsprozessen betrachtet. (IAB)
Keywords: S 1 Stufen der Berufsbildung; L 6.2.3 Evaluation; S 2.3 Berufsbildungspolitik; T 4.4 Politikwissenschaften; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; Berufsbildung; Wirkungsforschung; Berufsbildungspolitik; Berufsausbildung; Politikberatung; Kosten-Nutzen-Analyse